RESPON PERTUMBUHAN STEK BATANG VANILI (Vanilla planifolia) TERHADAP LAMA PERENDAMAN ZAT PENGATUR TUMBUH ROOT MOST - Wilhelmus Haman; Kristono Yohanes Fowo (Agriculture Faculty of Flores University, 2019)
This study aims to determine the response of the immersion time of vanilla stem cuttings in the most root growth regulating agent and to know the length of soaking time of the vanilla stem cuttings in the most optimum root growth regulator. The design used in this study was a Completely Randomized Design (CRD) with six treatments soaking in minutes. Repeated four times, namely P1 (10 minutes), P2 (20 minutes), P3 (30 minutes), P4 (40 minutes), P5 (50 minutes), P6 (60 minutes). Variables observed including the number of days of first shoot growth, the number of roots, root length, shoot diameter, shoot length, wet weight of cuttings, and dry weight of cuttings.The results showed that the treatment of P6 gave a very significant effect. On the variable growth in the number of roots (55.59%), root length (58.86%), number of days of first shoot growth (28 HST), shoot diameter (70.15%) , shoot length (71.43%), wet weight of cuttings (37.14%) and dry weight of cuttings (65.04%) at each age of observation.